Hybrid learning in EFL classes: attitudes, reasons, and implementation of the Indonesian millennial professors and Zen students - Dedi Turmudi; Muhamad Nova; Bambang Eko Siagiyanto (Journal on English as a Foreign Language, 2023)
The EFL professors and Zen students experienced dynamic learning during the pandemic. Thus, new scenarios in the new normal are required. This study investigates (1) what EFL millennial English professors (MEPs) and EFL Zen students (EZSs)' attitude to hybrid learning (HL), (2) why MEPs and EZSs need HL, and (3) how the MEPs and EZSs will implement the HL in New Normal. It is a survey study using a questionnaire that resulted in ordinal and content data. 174 MEPs and EZSs from diverse universities in Indonesia participated. The data were taken through online Google Forms and were analyzed descriptively based on critical success factors and criteria content analysis. The result shows that MEPs and EZSs responded positively (51.15%), neutrally (31.61%), and negatively (17.24%) to HL in EFL classrooms. The respondents think that HL is inevitable and challenging. The ratio online and offline is on-off (75:25), on-off (50:50), and on-off (25:75). The sequence of HL covers first-half all online, first-half all offline, in turn, online and offline, and in turn: offline and online. Most MEPs and EZSs (56.8 %) believe that HL is promising. The study carried out the proportional scenarios for HL; thus, MEPs and EZSs should be well prepared.